LiFePO4 particle conductive composite strategies for improving cathode rate capability. (1st May 2015) - Vicente, Nuria; Haro, Marta; Cíntora-Juárez, Daniel; Pérez-Vicente, Carlos; Tirado, José Luis; Ahmad, Shahzada; Garcia-Belmonte, Germà
Graphical abstract: Highlights: PEDOT decreases both charge-transference and LFP lithiation resistances. PEDOT addition by a blending method yields a specific capacity of 130 mA h gLFP −1 at 2 C. New insight into the role of conductive materias is obtained by EIS analysis. Abstract: Lithium iron phosphate (LFP) cathodes are one of the most promising candidates to find application in hybrid electric vehicle energy storage system. For this reason advances in the performance of its theoretical capacity at high charge/discharge rates is under continuous development. Most used strategies to improve power performance are the addition to the LFP particles of an electric conductive carbon or polymer, such as poly(3, 4-ethylenedioxythiophene) [PEDOT] doped with polystyrene sulfonate (PSS). The data obtained from impedance analysis provide new insight on the role of these additives that not only improve the charge transfer but also favor the lithiation/delithiation processes in the phosphate matrix. Furthermore, PEDOT is capable to reduce the resistances of charge transfer and lithiation reaction inside the phosphate matrix by one order of magnitude in comparison with those achieved with the carbon coating strategy. In this study, the most effective approach has been the addition of PEDOT by a blending method, resulting in a specific capacity of 130 mA h gLFP −1 at 2 C.